PENDAMPINGAN PERENCAAN PENGEMBANGAN BANGUNAN MADRASAH IBTIDAIYAH (MI) MUHAMMADIYAH 02 PEKANBARU - Boby Samra; David Setiawan; Hendri Silva (Komunitas Manajemen Kompetitif, 2025)
This community service was carried out through the development of a classroom design model located at Jl. Nila Gang AZ No. 7, Limbungan Baru Village, Rumbai Pesisir District, Pekanbaru City. This is a form of solution to the problems of space requirements, facilities, and land limitations available at the location, with the need for effective and efficient space resulting in a comfortable, safe, and contextual design. This design is expected to have an impact on the partner's problems in increasing the number of new students and also produce a design that complies with government regulations on building engineering, resulting in an educational building design that meets the needs that can be utilized for the construction process later. The implementation was carried out starting from conducting a location survey to identify space requirements, analyzing environmental aspects, architectural aspects, and drafting structural modules in the form of two-dimensional and three-dimensional drawings and animations. At each stage, presentations and discussions are held to obtain input so that the partner's problems can be resolved. The results of this building design are in the form of 2-dimensional and 3-dimensional spatial layout drawings. To maintain the continuity of the program, ongoing assistance will be provided. Keywords: Model, Spatial Layout, Effective, Efficient